The Bulldog Pride Fund to present 'Dear Harvey,' May 22-23 - Uribes, Tom::::::::: (2013)
Fresno State's Bulldog Pride Fund will present two performances of 'Dear Harvey,' 7:30-8:30 p.m. May 22-23, at The Painted Table in the Tower District.